Reexamining the Relationship Between Social Support and Depression Among First-Year University Students in Indonesia - Ratih, Annisa Tri; Kusumaningrum, Fitri Ayu (Unisia, 2025)
This study examines the relationship between social support and depression among first-year university students, a population widely recognized as vulnerable due to the psychological and social demands of transitioning into higher education. The primary objective is to analyze whether perceived social support is significantly associated with levels of depression in first-year students and to understand the direction and implications of this relationship. Using a quantitative, non-experimental correlational design, data were collected from 171 first-year students through standardized self-report instruments measuring depression and perceived social support from family, friends, and significant others. Because the data were not normally distributed, statistical analysis was conducted using Spearman correlation techniques. The results indicate a statistically significant but weak positive correlation between social support and depression, suggesting that higher levels of perceived social support were associated with higher levels of depressive symptoms. Further analysis across dimensions of social support revealed that family support showed the strongest correlation with depression compared to support from friends and significant others. These findings challenge the commonly held assumption that social support uniformly serves as a protective factor against depression. The discussion highlights that social support which is perceived as mismatched, pressuring, or emotionally unsupportive may instead contribute to psychological distress, particularly among students navigating early university adjustment. In conclusion, the study demonstrates that the effectiveness of social support depends not only on its presence but also on its quality and contextual relevance. The findings underscore the importance of developing mental health interventions and support systems that are responsive to students’ actual emotional needs rather than relying solely on increasing social support availability.